A major in science? Initial beliefs and final outcomes for college major and dropout - Ralph Stinebrickner; Todd Stinebrickner (The University of Western Ontario, CIBC Centre for Human Capital and Productivity, 2013)
Taking advantage of unique longitudinal data, we provide the first characterization of what college students believe at the time of entrance about their final major, relate these beliefs to actual major outcomes, and, provide an understanding of why students hold the initial beliefs about majors that they do. The data collection and analysis are based directly on a conceptual model in which a student's final major is best viewed as the end result of a learning process. We find that students enter school quite optimistic about obtaining a science degree, but that relatively few students end up graduating with a science degree. The substantial overoptimism about completing a degree in science can be attributed largely to students beginning school with misperceptions about their ability to perform well academically in science.
Keywords: 330; Education; College Major; Dropout; Science; Learning; Expectations Data